Analysis of the Existence of Traditional Markets Under the Threat of Modern Market Advances - Sri Wahyuni; Era Sonita; Zuhelmi Zuhelmi; Gina Havieza Elmizen (Peneliti.net, 2026)
This research aims to analyze the existence of traditional markets under the threat of modern market advancement, with a case study conducted at Tempurung Market, Kinali District, West Pasaman Regency. The phenomenon observed is the rapid development of modern markets such as minimarkets and supermarkets around the Kinali area, which potentially reduces the competitiveness and public interest in traditional markets. This study uses a qualitative approach with a descriptive method, employing observation, interview, and documentation techniques involving traders, buyers, and market managers. The results indicate that although the presence of modern markets has led to a decline in the number of buyers and income for some traders at Tempurung Market, traditional markets still maintain their distinctive appeal. The main factors sustaining their existence include more affordable prices, the bargaining system, close social relationships between traders and buyers, and the availability of fresh local products. Furthermore, most lower- and middle-income communities continue to rely on traditional markets as their primary place to meet daily needs. However, challenges such as limited facilities and infrastructure, suboptimal cleanliness, and minimal support from local governments in market revitalization remain significant issues. Therefore, greater government attention is needed, including infrastructure improvements, trader training, and the formulation of regulations that support traditional markets so that they can survive amid modern market competition.